The Effectiveness of Herbal Plant The Sambiloto Leaf (Andrographis paniculata) in Enhancing Body Immunity: A Literature Review - Nabila, Rana; Reisha Isaura, Emyr (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Immunity is one of the important things for the body's defense against viral and bacterial infections. In controlling the immune system, immunomodulators are needed, which usually come from compounds found in plants. Immunomodulatory compounds can be found in the leaves of the sambiloto plant. The content of sambiloto leaf compounds in the form of diterpenoids, flavonoids, and polyphenols is proven to be immunostimulants. Objective: This study aimed to determine the immunomodulatory effects of sambiloto leaves. Methods: This study used literature review method on in vivo and in vitro experimental studies that have been conducted. The article search used online databases Sciencedirect and Pubmed. Results: A total of eight articles were used in this study. Discussion: Based on the literature review, it is proven that sambiloto leaves have compounds that give rise to immunomodulatory effects. Conclusion: According to this study, the leaves of sambiloto (Andrographis paniculata) have the potential to be used as a herbal immunomodulatory medication that has anti-inflammatory and immune-enhancing effects. However, further research is needed to explore the molecular mechanism, more complex clinical trials, determine the optimal dose and dosage form of sambiloto leaves.